HUBUNGAN KEBUTUHAN PENGHARGAAN (ESTEEM NEEDS) DAN KOMPETISI DALAM BELAJAR (LEARNING OF COMPETITION) DENGAN KREATIVITAS BELAJAR FISIKA SISWA MTS MADANI ALAUDDIN PAO-PAO KABUPATEN GOWA - Hidayat, Yusuf (Universitas Islam Negeri Alauddin Makassar, 2018)
Abstract: Maslow in Poduska (2000: 201) defines the need for an esteem needs to be a person's desire for good judgment from others, to be respected and to receive praise from a teacher. Marcus Verrius Flaccus in Monks et al (1999: 279) argues that the learning competition is a learning activity, students competing for each other to get good learning outcomes. The existence of competition or student competition in the learning process (learning of competition) is one of the strong factors in motivating students in learning. Barro in Ali and Asrori (2006: 41) that creativity is the ability to create something new, something new does not mean to be entirely new, but can also be a combination of elements that have been there before. This study aims to describe and interpret the relationship of the need for awards (esteem needs) and competition in learning (learning of competition) with students' physics learning creativity MTs Madani Alauddin Pao-Pao Gowa District. The type of this research is descriptive correlational research. The population of this study is all students of MTs 2012/2013 school year. The sample using Proportional Stratified Random Sampling technique is by taking representative sample where the researcher takes 25% from the existing population that is 40 students from 160 students of MTs Madani Alauddin Pao-Pao Gowa District and with sampling based on grade level then taken at random. To obtain the data of researchers using questionnaires and interview guides conducted by researchers to physics teachers of each class. Data analysis techniques used are descriptive statistics and inferential statistics for hypothesis testing.